Severe Acute Kidney Injury Following Stage 1 Norwood Palliation: Effect on Outcomes and Risk of Severe Acute Kidney Injury at Subsequent Surgical Stages*. Issue 7 (July 2016) - Wong, Joshua H.; Selewski, David T.; Yu, Sunkyung; Leopold, Kay E.; Roberts, Katelyn H.; Donohue, Janet E.; Ohye, Richard G.; Charpie, John R.; Goldberg, Caren S.; DeWitt, Aaron G.
Abstract : Objectives: To identify associations of severe acute kidney injury early after stage 1 (Norwood) operation with risk of severe acute kidney injury and comorbidities at subsequent palliative stages in patients with hypoplastic left heart syndrome and other single ventricle lesions with left-sided obstruction. Design: Retrospective cohort study. Severe acute kidney injury defined as Kidney Disease Improving Global Outcomes stage 3. Setting: Single pediatric cardiac center. Patients: Infants less than or equal to 28 days old with single ventricle physiology and left-sided obstruction undergoing stage 1 operation between September 2007 and November 2012 ( n = 136). Interventions: None. Measurements and Main Results: The occurrence rate of severe acute kidney injury was 21% (28/136) following stage 1, 12% (12/98) following stage 2 palliation (superior cavo-pulmonary anastomosis), and 10% (7/73) following stage 3 palliation (total cavo-pulmonary anastomosis). Severe acute kidney injury early after stage 1 operation was significantly associated with continuous intravenous loop diuretic infusion, need for extracorporeal membrane oxygenation, and in-hospital death (all p < 0.05). Gestational age at birth was associated with severe acute kidney injury at stage 2 ( p = 0.04) and stage 3 ( p = 0.01). Severe acute kidney injury at stage 1 was an independent risk factor for severe acute kidney injury at stage 2 (adjusted odds ratio, 4.3; 95% CI, 1.1–16.9; p = 0.04). Development of severe acute kidney injury after stage 1 was associated with longer mechanical ventilation time after stage 3 ( p = 0.047). Conclusions: Severe acute kidney injury after stage 1 palliation was an independent risk factor for developing severe acute kidney injury at stage 2, and was associated with prolonged duration of mechanical ventilation following stage 3. Information on the incidence and associated risk factors for postoperative acute kidney injury in hypoplastic left heart syndrome patients from multiple congenital heart centers is a necessary next step to further understand the long-term burden of severe acute kidney injury after staged palliation.